Study of the investment attractiveness of human capital of the Donetsk People's Republic - E. S. Shilets; A. O. Sukhinina (Вестник Северо-Кавказского федерального университета)
The article presents directions for investing in the human capital of the Donetsk People's Republic (DPR). The data on the population of the DPR are provided. Further, the education and healthcare systems of the Republic are studied. The dynamics of changes in the number of students in secondary educational institutions of the DPR is considered. The demand and supply of labor in the DPR are also analyzed, the dynamics of the situation in the labor market is reflected. Materials and methods of research. The study is based on the analysis of statistical data, as well as publications in scientific journals, collections and reports. Research results and their discussion. The study aimed to identify the main areas for investing in the human capital of the DPR, to study data on the population, as well as education and healthcare systems, and to study the situation on the labor market. For this, an analysis of literary, statistical sources and Internet resources was carried out. Thus, among the main areas for investment in human capital, the following can be distinguished: education and training, healthcare, entrepreneurship and small business development, infrastructure and technology. The population of the DPR in 2022 amounted to 2202.4 thousand people. There are three levels in the education system of the Republic: general secondary, vocational and higher vocational education. The healthcare system is facing a severe shortage of staff. In 2022, the coefficient of tension in the labor market of the DPR was 0.9. Conclusion. Based on the results of the study, it can be concluded that ensuring the investment attractiveness of the human capital of the DPR is an important task. Human capital, as an independent resource, ensures the competitiveness and stability of the national economy.